LEVEL CROSSINGS AT RAILWAYS - Zafirovski Zlatko; Ognjenovic Slobodan; Gacevski Vasko; Nedevska Ivona; Nedevska Ivana (UNIVERSITY OF MONTENEGRO FACULTY OF CIVIL ENGINEERING, 2020)
The intersection of railways with other roads can be designed in different ways, according to the needs, conditions, possibilities and regulations. Level or grade crossing is one of the solutions used in civil engineering. These areas pose inherent hazards to train operations, as they do to motor vehicles, non‐motorized vehicles and pedestrians. Generally, new crossings (particularly on mainline tracks) should not be permitted unless no other viable alternatives exist. Even in those instances, consideration should be given to closing one or more existing crossings. When there is no other alternative, provisions must be made to ensure that the roadway approaches and crossing surface are suitable for all traffic, that sufficient warning is provided of the approach of trains, and that management of the this type of intersection is coordinated with other intersections involving nearby roads. Various types of level crossing structures and equipment can be used, each providing different technical and safety design. This paper shows different approaches and regulations used throughout the world and various types of level crossing structures and systems.
Keywords: Railways, roads, intersection, level crossing, crossing structures